Prevalence And Antimicrobial Susceptibility Patterns Of Bacteria Isolated From Urinary Tract Infections (UTIs) In Children At Children Hospital In Baghdad - Hussein, Nadheema Hammood (AL-Kindy College Medical Journal, 2019)
Background: First six to twelve months after initial urinary tract infection, most infections are caused by Escherichiacoli, although in the first year of life Klebsiella pneumoniae, Pseudomonas, Enterobacter spp andEnterococcus spp, are more frequent than later in life, and there is a higher risk of urosepsis compared with adulthood Objectives: To determine the prevalence of bacterial isolates from Urinary Tract Infections of children at a children hospital in Baghdad and their antimicrobial susceptibility patterns. Type of the study: Cross-sectional study. Methods: During six months of study (1 June to 31 December, 2016), 117urine specimens were collected from a children hospital in Baghdad. Results: Out 38 isolates of Gram positive and Gram negative bacteria were obtained from urine specimens in a percentage of 5(13.2%) and 33(86.8%),respectively. The lowest incidence was among the 11-15 years old age group (11.9%) whereas the highest incidence was among the 1-5 years old age group (43.6%)(P≤0.05).Also out of 38positive cultures, the incidence was higher in females 31(81.6%)than that of males 7(18.4%). Out of 38 positive cultures, the isolation rate was 5(13.2%) for Gram positive isolates and 33(86.8%)for Gram negative isolates. The most frequently isolated bacteria was Escherichia coli19(50%)(P-value ≤ 0.05), while the only isolated Gram positive was Staphylococcus aureus5(42.86%) isolates.The most effective antibiotics for Staphylococcus aureus isolates were Vancomycin and Amikacinfor (100%) and for Gram negative isolates wasimipenem (100%). Ampicillin showed the highest resistance rate for both Gram positive and Gram negative isolates(100%) and Pesudomonas aeruginsa isolates showed the highest resistant rates to most antibiotics under study. Conclusions: The most frequently isolated bacteria was E. coli from all urine cultures and the most effective antibiotics for Staphylococcus aureus isolates were Vancomycin and Amikacinfor